Light over the dark continent - Tatford, Frederick Albert, 1901-; Echoes of Service (Bath, UK Echoes of Service, 1984)
Includes indexes, biographical details, maps, photographs, etc.
Brethren writer.
Keywords: Brethren movement -- missions -- Africa -- history